Mucolipidosis types II and III and non-syndromic stuttering are associated with different variants in the same genes - Raza, M. Hashim; Domingues, Carlos Ef; Webster, Ronald; Sainz, Eduardo; Paris, Emily; Rahn, Rachel; Gutierrez, Joanne; Chow, Ho Ming; Mundorff, Jennifer; Kang, Chang-soo; Riaz, Naveeda; Basra, Muhammad A. R.; et al. (Nature Publishing Group, 2016)
Homozygous mutations in GNPTAB and GNPTG are classically associated with mucolipidosis II (ML II) alpha/beta and mucolipidosis III (ML III) alpha/beta/gamma, which are rare lysosomal storage disorders characterized by multiple pathologies. Recently, variants in GNPTAB, GNPTG, and the functionally related NAGPA gene have been associated with non-syndromic persistent stuttering. In a worldwide sample of 1013 unrelated individuals with non-syndromic persistent stuttering we found 164 individuals who carried a rare non-synonymous coding variant in one of these three genes. We compared the frequency of these variants with those in population-matched controls and genomic databases, and their location with those reported in mucolipidosis. Stuttering subjects displayed an excess of non-synonymous coding variants compared to controls and individuals in the 1000 Genomes and Exome Sequencing Project databases. We identified a total of 81 different variants in our stuttering cases. Virtually all of these were missense substitutions, only one of which has been previously reported in mucolipidosis, a disease frequently associated with complete loss-of-function mutations. We hypothesize that rare non-synonymous coding variants in GNPTAB, GNPTG, and NAGPA may account for as much as 16% of persistent stuttering cases, and that variants in GNPTAB and GNPTG are at different sites and may in general, cause less severe effects on protein function than those in ML II alpha/beta and ML III alpha/beta/gamma.